PENGARUH CITRA MEREK DAN LOYALITAS MEREK TERHADAP EKUITAS MEREK PADA SABUN MUKA CITRA DI KALANGAN MAHASISWA DI KOTA SUNGAI PENUH - Anggia Ayu Lestari (Jurnal Ekonomi Sakti, 2022)
This study aims to analyze the influence of brand image and brand loyalty of Citra facial soap among college students in the City of Sungai Penuh. This type of research is causative research. This research was conducted in the City of Sungai Full. The population in this study were students in the City of Sungai Penuh. Samples were taken by purposive sampling using the Slovin formula, with a total sample of 100 people. Data collection technique is to use a questionnaire. The data analysis technique used was hypothesis testing and multiple linear regression analysis. The results of this study indicate that: 1) brand image has a significant effect on brand equity in Citra facial soap among university students in Sungai Penuh City and 2) brand loyalty has no significant effect on brand equity in Citra facial soap among students in Sungai Pemuh City.